Development of a typical infrastructure for a quantum random number generator web service - Morhul, D.M.; Nariezhnii, O.P.; Hrinenko, T.O. (Radiotekhnika, 2025)
Quantum Random Number Generators (QRNGs) provide physically unpredictable entropy essential for cryptography, modeling, and scientific research. Local generation is preferred for the highest level of security, as it eliminates the risks associated with transmitting data over a network. At the same time, public QRNG web services accessible via the API serve as a valuable tool in cases where dedicated hardware is unavailable, enabling rapid integration into software prototypes, statistical testing, large-scale simulations, and educational projects. Combining local and remote sources makes it possible to optimize the balance between security, accessibility, and performance. This article helps to develop and justify a typical QRNG web service infrastructure, which includes functional components, security requirements, access interfaces (API), methods for quality control of randomness, and recommendations for scalability. The proposed infrastructure is intended to serve as a foundation for creating interoperable, secure, and efficient web services of quantum entropy sources.